2021
DOI: 10.1057/s41599-021-00989-2
|View full text |Cite|
|
Sign up to set email alerts
|

Doing well by doing good with the performance of United Nations Global Compact Climate Change Champions

Abstract: Are Climate Change Champions favorable to investors? This is the first study of portfolio performance of a fourth generation SRI screening strategy based on United Nations Global Compact firms who are Climate Change Champions. The operational changes made by UNGC firms are real and disproves the notion that UNGC firms are merely green-washing. We find that after firms join UNGC, there is a positive effect on long term portfolio performance. UNGC firms have lower volatility and so less risk than their competito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…Se demostró que tanto las tres dimensiones de la RSE como los constructos IMA y REP son válidos, pues una vez depuradas las escalas, se demostró la fiabilidad de sus ítems y, también, la confiabilidad de las variables latentes del modelo global, así como la validez convergente y discriminante de los mismos. El resultado de las dimensiones de la RSE concuerda con los postulados de una corriente importante de la RSE, según la cual ésta se encuentra estrechamente ligada al DS (Agirre & Gómez, 2019;Alvarado, 2008;Ashrafi et al, 2020;Días et al, 2018) y, por ello, es aplicable en el negocio petrolero (Hancock, 2005;Msiska et al, 2021;Vargas et al, 2022). Al analizar con detalle se observa que el apoyo y mejora de calidad de vida de las comunidades locales donde realiza operaciones (Soc1 y 5) son los únicos indicadores percibidos como iniciativas de RSE por el grupo de interés consultado, no así lo atinente a las responsabilidades con los trabajadores o cultura, educación y deporte, cuyos ítems no resultaron válidos, lo cual coincide con las dos primeras aseveraciones de Msosa (2023) de que en épocas de crisis es una práctica común en las industrias extractivas colocar el bienestar y los derechos de los trabajadores, así como a las comunidades en un lugar más bajo de la lista de prioridades.…”
Section: Discusión De Resultados Y Conclusionesunclassified
“…Se demostró que tanto las tres dimensiones de la RSE como los constructos IMA y REP son válidos, pues una vez depuradas las escalas, se demostró la fiabilidad de sus ítems y, también, la confiabilidad de las variables latentes del modelo global, así como la validez convergente y discriminante de los mismos. El resultado de las dimensiones de la RSE concuerda con los postulados de una corriente importante de la RSE, según la cual ésta se encuentra estrechamente ligada al DS (Agirre & Gómez, 2019;Alvarado, 2008;Ashrafi et al, 2020;Días et al, 2018) y, por ello, es aplicable en el negocio petrolero (Hancock, 2005;Msiska et al, 2021;Vargas et al, 2022). Al analizar con detalle se observa que el apoyo y mejora de calidad de vida de las comunidades locales donde realiza operaciones (Soc1 y 5) son los únicos indicadores percibidos como iniciativas de RSE por el grupo de interés consultado, no así lo atinente a las responsabilidades con los trabajadores o cultura, educación y deporte, cuyos ítems no resultaron válidos, lo cual coincide con las dos primeras aseveraciones de Msosa (2023) de que en épocas de crisis es una práctica común en las industrias extractivas colocar el bienestar y los derechos de los trabajadores, así como a las comunidades en un lugar más bajo de la lista de prioridades.…”
Section: Discusión De Resultados Y Conclusionesunclassified
“…Torre et al (2020) analyzed the Eurostoxx50 index performance for the period of 2010-2018 according to their ESG scores and concluded that the performance of the aforementioned index does not seem to be affected by the ESG commitments. Msiska et al (2021) Zehir and Aybars (2020) conducted their study in Europe and Turkey and found no association between SRI and portfolio performance. The CAPM analysis demonstrated that ESG-based portfolios are behind the market index.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Torre et al (2020) analyzed the Eurostoxx50 index performance for the period of 2010–2018 according to their ESG scores and concluded that the performance of the aforementioned index does not seem to be affected by the ESG commitments. Msiska et al (2021) recommended investing in UN Global Compact Climate Change Champions firms, finding no underperformance penalty as compared to a standard portfolio because the lower return indicates lower risk. Bermejo Climent et al (2021) demonstrated the influence of ESG disclosure on the performance of European corporate equities.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%